2010
DOI: 10.1021/cm1017344
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Monodisperse Spherical MCM-48 Mesoporous Silica Nanoparticles with Controlled Particle Size

Abstract: A rapid and facile synthesis route to the monodisperse spherical MCM-48 mesoporous silica nanoparticles (MSN) with cubic Ia3̅d mesostructure is developed based on the modified Stöber method. The phase domain of MCM-48-type MSNs can be extended by controlling the stirring rate and molar ratios of silica source and surfactant. The formation of monodispersed spherical MCM-48-type MSNs is obtained using triblock copolymer Pluronic F127 as a particle size designer. The average size of monodisperse spherical MSN ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
236
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(242 citation statements)
references
References 62 publications
6
236
0
Order By: Relevance
“…Moreover, Lin et al demonstrated that the MCM-48-type MSNs diameter ranging from 70-500 nm can be obtained by adding different amounts of Pluronic F127. They also used CTAB, Pluronic F127, NH 4 OH and TEOS to synthesis MCM-48-type MSNs [88].…”
Section: Grun Et Al Redesign Stober Methods By Changing the Compositionmentioning
confidence: 99%
“…Moreover, Lin et al demonstrated that the MCM-48-type MSNs diameter ranging from 70-500 nm can be obtained by adding different amounts of Pluronic F127. They also used CTAB, Pluronic F127, NH 4 OH and TEOS to synthesis MCM-48-type MSNs [88].…”
Section: Grun Et Al Redesign Stober Methods By Changing the Compositionmentioning
confidence: 99%
“…The cubic porous network has advantages over hexagonal networks as theorized by Monnier et al [43] With the intertwined porous structure, diffusion and transport within the mesoporous network is not hindered with pore blockage as it is seen in the well-ordered hexagonal crystalline structure. The synthesis of cubic MCM-48 observed by Kim et al [44] was produced with both pure CTAB as a template, but only seen with higher stir speeds and low surfactant to silicon ratio. Presence of a co-solvent, ethanol, also drives the conversion of hexagonal to cubic symmetry as well [45].…”
Section: Non-ionic and Amphiphilic Surfactantsmentioning
confidence: 99%
“…At the first step, mesoporous carbon nanoparticles were synthesized referring to the literatures with some modification through a modified Stöber method [30,31].…”
Section: Preparation Of Mesoporous Carbon-enriched Palladium Nanostrumentioning
confidence: 99%